Consumers' Opinions and Expectations of an “Ideal Chicken Farm” and Their Willingness to Purchase a Whole Chicken From This Farm - Escobedo del Bosque, Cynthia I.; Risius, Antje; Spiller, Achim; Busch, Gesa (Frontiers in Animal Science, 2021)
As poultry production and consumption have increased in the last decade, so have consumers’ concerns about intensified production methods and the impacts they have on animal welfare. At the same time, poultry consumption has increased and enjoys great popularity. Also, a shift in consumers’ consumption behaviour can be observed as nowadays most consumers purchase chicken cuts, especially breast fillets, rather than whole animals, mostly due to convenience and taste. Although consumer concerns have increased, market shares of alternative poultry products, i.e. those that are produced under higher standards compared to conventional products, remain comparably low. One of the main reasons are the large differences in prices. The higher prices for alternative chicken products such as organic result partly from increased production costs on farm level. Besides, consumer preferences for chicken cuts intensify cost differences. While alternative chicken breasts (e.g. organically produced) might be valued by some consumers, other cuts such as wings or thighs are not and are therefore sent into the conventional market. In these cases, the breasts need to remunerate all additional costs. Analysing consumers’ concerns about production methods and learning about consumers’ obstacles to buy whole chickens might offer farmers greater possibilities to succeed in alternative markets. Therefore, the purpose of this study was to gain insights into consumers’ chicken consumption behaviours, how consumers imagine an ideal chicken farm and whether they would be willing to purchase a whole chicken from this ideal farm. Three focus group discussions (total n=30) with German consumers were held online in June 2020. The results show that participants associate the ideal chicken farm with four main characteristics: good husbandry system, positive economic impact for the farmer, high transparency, and proximate location of the farm in the same geographical region. However, willingness to purchase a whole chicken, even from the ideal farm, remains low due to mainly convenience reasons and daily routines.